Angestellte und selbstständige Fachärzte in der vertragsärztlichen ophthalmologischen Versorgung - Hahn, Ursula; Kretz, Florian Tobias Alwin (Der Ophthalmologe, 2018)
AimThe aim of the study was to evaluate the contribution to outpatient care and the perspectives of employed and self-employed ophthalmologists in isolation and in comparison to other professional groups.MethodBased on statistical data (source: statistical information provided by the National Association of Statutory Health Insurance Physicians) from 31 December 2015, newly admitted physicians in 2015 and their contribution differentiated by employment relationships were evaluated according to head count and working time equivalents (using “planning of demand equivalents”). The results were subdivided into type of outpatient facility, e.g. single practice, group practice and medical care centers (MVZ).ResultsThe proportion of employed ophthalmologists (head count) in outpatient care (23%) and newly admitted physicians (81%) is above the interdisciplinary average (16% and 65%, respectively). In all medical professional groups the contribution according to time equivalents of employed physicians compared to self-employed physicians is lower (utilization rate: 65% in total and 70% in ophthalmology). In ophthalmology employment is seen in all types of outpatient practices: the number of ophthalmologists working in group practices is above average, compared to other groups they are underrepresented in MVZ and are working in single practices as frequently as all other specialties.Discussion and conclusionEmployment of physicians is more common in all types of outpatient ophthalmological facilities than in other specialized professional groups. Possible reasons are the working conditions in ophthalmology attracting physicians preferring employment and the competitive situation for practice takeover. Since employed physicians contribute less time to medical care than self-employed physicians, ophthalmology has a higher risk of a shortage in medical care despite an increasing number of physicians. An increasing number of employed physicians has an impact on the structures of outpatient care; however, the intensity of concentration in healthcare structures can only be partially evaluated due to insufficient data. Based on the available data there is no end in sight for the trend towards employment in outpatient ophthalmological care.